ChemInform Abstract: Catalyst‐Free One‐Pot Access to 3‐Pyrazolylisoindolinone Derivatives. Issue 11 (February 2016) - Che, Fengfeng; Fu, Zhijie; Shen, Tianhua; Lin, Yan; Song, Qingbao
Abstract: The title compounds are synthesized by a three‐component reaction of 2‐formylbenzoic acids, pyrazolones, and primary amines (26 examples) or ammonium hydroxide (6 examples) under catalyst‐free conditions.